The basics of the Philippine criminal justice system - Capulso, Nierme A. Jr; Saluba, Dennis J. (C & E Publishing, Inc., 2016)
"Written for students enrolled in criminology courses and programs, as well as for researchers and other professionals interested in the study of crime, criminals, and criminal law, The basics of the Philippine criminal justice system provides general overview of the Philippine criminal justice system. Aside from extensive discussions on the nature of law enforcement, the duties and responsibilities of law enforcers, and the dual role of prosecutors as investigators of crimes and officers of the court, this textbook also contains chapters on the organizational structure of Philippine courts, the reformative task of correctional institutions, and society's part in the rehabilitation of former convicts. End-of-chapter exercises are also included to check and reinforce student's comprehension"--Cover.